The m6A Methylation Profile Identified That OsHMT9.1 Deregulates Chromium Toxicity in Rice (Oryza sativa L.) Through Negative Regulatory Functions - Yushan Hou; Xuejiao Kong; Jingwen Li; Changsheng Liu; Shuo Wang; Shupeng Xie; Jingguo Wang; Hualong Liu; Lei Lei; Hongliang Zheng; Wei Xin; Detang Zou; et al. (Agriculture)
Chromium (Cr) is a toxic heavy metal that affects the food chain and poses a severe threat to food safety. Nonetheless, the N6-methyladenosine (m6A) transcriptomic regulation mechanisms of Cr tolerance genes in rice are not well understood. This study found that rice roots exhibit competitive and synergistic interactions with trace elements under Cr stress. Through a comprehensive transcriptome analysis of m6A methylation profiles under Cr stress, differentially methylated genes (DMGs) closely related to the plasma membrane, oxidoreductase activity, and protein phosphorylation were identified. A significant number of differentially expressed genes (DEGs) associated with heavy metal transporter domains, metalloproteases, metal ion transporters, and other cation transporters were strongly induced by Cr. Additionally, OsHMT9.1 exhibited extensive hypomethylation and up-regulation in Cr-exposed roots and was confirmed to be a regulatory factor for Cr tolerance. Enhanced plant resistance to Cr in oshmt9.1 was accompanied by increased levels of P, K, S, and Ca and decreased levels of Mn and Cu. These results suggest that knocking out OsHMT9.1 can promote Cr detoxification in rice by modulating the balance between Cr and other trace elements. These findings provide new insights into the molecular regulation and stress response of rice under Cr stress through transcriptome m6A methylation patterns.